1999
DOI: 10.1038/sj.sc.3100902
|View full text |Cite
|
Sign up to set email alerts
|

Ependymomas of the spinal cord and cauda equina: An analysis of 26 cases and a review of the literature

Abstract: Study design: Retrospective review. Objectives: To clarify the clinical features of patients with spinal ependymomas and to compare the clinical results between the patients in whom microsurgical technique and spinal cord monitoring were used intraoperatively and the patients in whom they were not used. Setting: Keio University Hospital, Tokyo, Japan. Methods: Twenty-six consecutive patients with spinal ependymomas were treated surgically between 1958 and 1995. All patients underwent tumor resection through a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
44
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 14 publications
0
44
0
2
Order By: Relevance
“…Advances in surgical technique and the routine use of corticosteroids has lead to reduced morbidity and mortality, however, the role of adjuvant radiotherapy after spinal ependymoma surgery remains unclear. Some authors have suggested post-operative radiotherapy following complete excision [13,19,21], whilst many feel that adjuvant therapy is unnecessary after complete excision [1,2,6]. When technical reasons prevent complete excision or in cases with metastatic spread, radiotherapy is advocated [4,8], however, concerns that radiotherapy may cause reactive gliosis and fibrosis making re-operation for recurrence technically difficult [10], and concern about long-term radiation myelopathy leading to severe neurological dysfunction [16,22] have limited its use in some centres.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in surgical technique and the routine use of corticosteroids has lead to reduced morbidity and mortality, however, the role of adjuvant radiotherapy after spinal ependymoma surgery remains unclear. Some authors have suggested post-operative radiotherapy following complete excision [13,19,21], whilst many feel that adjuvant therapy is unnecessary after complete excision [1,2,6]. When technical reasons prevent complete excision or in cases with metastatic spread, radiotherapy is advocated [4,8], however, concerns that radiotherapy may cause reactive gliosis and fibrosis making re-operation for recurrence technically difficult [10], and concern about long-term radiation myelopathy leading to severe neurological dysfunction [16,22] have limited its use in some centres.…”
Section: Discussionmentioning
confidence: 99%
“…1,11,15,19,34,42 Many developments have occurred since IOM was first used, 8 and currently SSEPs are used to assess the dorsal afferent tracts, 35 while MEPs are used for monitoring the motor tracts of the spinal cord. The utility and accuracy of each monitoring modality may be affected by the type of surgery, patient condition, anesthesia, and physiological changes during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified extent of resection as an important variable. [1][2][3][4][5][6][7][8][9] Young age at diagnosis is a poor prognostic factor, although a clear explanation for this observation has not been proposed. …”
mentioning
confidence: 99%